Racial/Ethnic Disparities in Mortality Across the Veterans Health Administration - Michelle S. Wong; Katherine J. Hoggatt; W. Neil Steers; Susan M. Frayne; Alexis K. Huynh; Elizabeth M. Yano; Fay S. Saechao; Boback Ziaeian; Donna L. Washington (Mary Ann Liebert, 2019)
Purpose: Equal-access health care systems such as the Veterans Health Administration (VHA) reduce financial and nonfinancial barriers to care. It is unknown if such systems mitigate racial/ethnic mortality disparities, such as those well documented in the broader U.S. population. We examined racial/ethnic mortality disparities among VHA health care users, and compared racial/ethnic disparities in VHA and U.S. general populations. Methods: Linking VHA records for an October 2008 to September 2009 national VHA user cohort, and National Death Index records, we assessed all-cause, cancer, and cardiovascular-related mortality through December 2011. We calculated age-, sex-, and comorbidity-adjusted mortality hazard ratios. We computed sex-stratified, age-standardized mortality risk ratios for VHA and U.S. populations, then compared racial/ethnic disparities between the populations. Results: Among VHA users, American Indian/Alaskan Natives (AI/ANs) had higher adjusted all-cause mortality, whereas non-Hispanic Blacks had higher cause-specific mortality versus non-Hispanic Whites. Asians, Hispanics, and Native Hawaiian/Other Pacific Islanders had similar, or lower all-cause and cause-specific mortality versus non-Hispanic Whites. Mortality disparities were evident in non-Hispanic-Black men compared with non-Hispanic White men in both VHA and U.S. populations for all-cause, cardiovascular, and cancer (cause-specific) mortality, but disparities were smaller in VHA. VHA non-Hispanic Black women did not experience the all-cause and cause-specific mortality disparity present for U.S. non-Hispanic Black women. Disparities in all-cause and cancer mortality existed in VHA but not in U.S. population AI/AN men. Conclusion: Patterns in racial/ethnic disparities differed between VHA and U.S. populations, with fewer disparities within VHAs equal-access system. Equal-access health care may partially address racial/ethnic mortality disparities, but other nonhealth care factors should also be explored.